The strange message in the parchment - Keene, Carolyn (New York : Grosset & Dunlap, 2006)
While trying to recover a set of stolen parchment paintings, Nancy Drew becomes involved in tracking a kidnapper and extortionist.
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Detective and mystery stories, American; Van Devier Collection